Rotations and Levels of Reasoning, according to the Van Hiele model: Results of an Experience - Sarrín Suárez, Mercedes Maritza (2019)
This article presents the results of a qualitative research of ethnographic design, carried out with eight (8) students of fifth grade of the Fernando Belaúnde Terry secondary school of Ate, the objective of the investigation was to know the development of the geometric thought of rotations in the students, according to the Van Hiele model. The data collection was done through a follow up to the development of the activities programmed in the rotation-learning module designed according to the Van Hiele model, the formative test of open answers and the mixed interview. The results show that students mostly exhibited characteristics of level 2 (analysis) with a good path towards the acquisition of characteristics of level 3 (classification).